Análisis y valuación de puestos para la optimización de los costos de personal operativo en el Hipermercado Metro Canadá - Alarcón Quintana, Dolly Karito (2023)
This research "THE ANALYSIS AND VALUATION OF POSITIONS FOR THE OPTIMIZATION OF OPERATIONAL PERSONNEL COSTS IN THE METRO CANADA HYPERMARKET" aims to perform the analysis and valuation of positions based on a score of factors to optimize the cost of operating personnel in the Metro Canada hypermarket. The analysis and valuation were carried out by applying the point-factor method after an internal and external analysis of the store and preparation of the position descriptions under study. Nine factors that met the criteria of importance, differentiation, and independence were chosen. With these factors, each position was evaluated. In order to make the evaluation as objective and impartial as possible, a statistical analysis was done. Afterwards, the remunerations were graphed versus the score of each position with different trend lines that would allow finding the most exact equation for the calculation of the new remunerations, the equation with the highest correlation coefficient was chosen. After estimating the new remunerations, four categories were proposed for the new remuneration structure, which proposes salary ranges with better internal equity for each category. Finally, the results were analyzed, and it was concluded that the application of this study has a positive impact on the management of the Metro Canada Hypermarket, through the implementation of more equitable salary ranges that lead to a reduction in operating personnel costs.